Evaluasi Dan Peningkatan Prestasi Belajar Siswa Dengan Sistem Pakar Berbasis Fuzzy - RIJAL PAIZAL (JURNAL ILMU PENGETAHUAN & SISTEM INFORMASI (JIPSI), 2018)
ABSTRACT Fuzzy logic is a tool in an expert system that can assist in addressing the causes of failure of students in an educational evaluation. By analyzing the objects that have been determined to obtain the required data in the process of evaluation and improvement analysis of student achievement. The values ​​of variables in the form of cognitive value, value Psychomotor, and Affective Value. So that these values ​​will be used as a rule that will be used in expert systems. After analysis of these variables can dig diaharapkan values ​​of rule-based knowledge for later use in fuzzy logic Mandani. For the implementation of activities previous analysis by the method of rulebased expert system, then designed a simple application program using MATLAB programming language that uses Fuzzy Logic method Mandani. Fuzzy logic will provide the desired information by using the rule base is varied. Thus acquired a knowledge of how to determine what the cause of the failure of students in an evaluation of education and how to cope with the failure of these students. Keywords: Fuzzy Logic, Applications Matlab, Affective Value Data, Value Data Cognitive, Psychomotor Value Data.